Effects of body-mapping-designed clothing on heat stress and running performance in a hot environment - Jiao, J.; Li, Y.; Yao, L.; Chen, Y.; Guo, Y.; Wong, S. H. S.; Ng, F. S. F.; Hu, J. (Ergonomics, 2017)
To investigate clothing-induced differences in human thermal response and running performance, eight male athletes participated in a repeated-measure study by wearing three sets of clothing (CloA, CloB, and CloC). CloA and CloB were body-mapping-designed with 11% and 7% increased capacity of heat dissipation respectively than CloC, the commonly used running clothing. The experiments were conducted by using steady-state running followed by an all-out performance running in a controlled hot environment. Participants` thermal responses such as core temperature (Tc), mean skin temperature (), heat storage (S), and the performance running time were measured. CloA resulted in shorter performance time than CloC (323.1 ± 10.4 s vs. 353.6 ± 13.2 s, p = 0.01), and induced the lowest , smallest ?Tc, and smallest S in the resting and running phases. This study indicated that clothing made with different heat dissipation capacities affects athlete thermal responses and running performance in a hot environment.